Hydroxychloroquine as Treatment for Inflammatory Subglottic Stenosis: A Second Successful Case. (6th November 2012) - Desuter, G.; Gregoire, A.; Gardiner, Q.; Houssiau, F.
Abstract : Inflammatory sub-glottic stenosis is a life threatening condition that represents a therapeutic challenge. Recently, hydroxychloroquine has been suggested as one efficient medical treatment option. This report describes the second case of successful treatment of inflammatory sub-glottic stenosis using hydroxychloroquine.